Está en la página 1de 17

k

E E' E = +
2
0
m c ( ' ) h h 1 v v ¸ ÷ = +
2
0
m
C C
h h
'
c ( 1)
ì ì
¸ = ÷ +
0
m c
h
)
'
1
h
(
ì ì
¸ = ÷ +
….…Ec.1
h '
C
v
h '
sen
C
v
u
h '
cos
C
v
u
0
m V ¸
0
m V cos ¸ |
0
m Vsen ¸ |
h
C
v
h '
C
v
h '
sen
C
v
u
h '
cos
C
v
u
0
m V ¸
0
m V cos ¸ |
0
m Vsen ¸ |
h
C
v
E
P P' P = +
h '
C
v
h '
sen
C
v
u
h '
cos
C
v
u
0
m V ¸
0
m V cos ¸ |
0
m Vsen ¸ |
h
C
v
0
h h '
cos m V cos
C C
v v
u ¸ | = +
h '
C
v
h '
sen
C
v
u
h '
cos
C
v
u
0
m V ¸
0
m V cos ¸ |
0
m Vsen ¸ |
h
C
v
0
C C
h h
'
cos V cos
C C
m
ì ì
u ¸ | = +
h '
C
v
h '
sen
C
v
u
h '
cos
C
v
u
0
m V ¸
0
m V cos ¸ |
0
m Vsen ¸ |
h
C
v
0
h h
c c
'
m os V os u ¸ |
ì ì
= +
…Ec.2
h '
C
v
h '
sen
C
v
u
h '
cos
C
v
u
0
m V ¸
0
m V cos ¸ |
0
m Vsen ¸ |
h
C
v
0
h '
sen Vsen m
C
v
u ¸ | =
h '
C
v
h '
sen
C
v
u
h '
cos
C
v
u
0
m V ¸
0
m V cos ¸ |
0
m Vsen ¸ |
h
C
v
0
C
h
sen Vsen m
C
ì
u ¸ | =
h '
C
v
h '
sen
C
v
u
h '
cos
C
v
u
0
m V ¸
0
m V cos ¸ |
0
m Vsen ¸ |
h
C
v
0
h
sen Vse m n u ¸ |
ì
=
…Ec.3
COMBINANDO ADECUADAMENTE LAS
TRES ECUACIONES:
0
m c
h
)
'
1
h
(
ì ì
¸ = ÷ +
….…Ec.1
0
h h
c c
'
m os V os u ¸ |
ì ì
= +
…Ec.2
0
h
sen Vse m n u ¸ |
ì
=
…Ec.3
SE OBTIENE:
0
h
(1 cos )
m C
ì u A = ÷
DONDE:
12
C
0
h
2.43 10 m
m C
ì
÷
= = ×

.

E  E'  E k h  h '  m0 c (   1 ) 2 .

C 2 h h  m0 c (   1)  ' C .

h   m0 c(   1 )  ' h ….1 .…Ec.

h ' C h ' cos  C h ' sen C h C  m0V cos   m0V  m0Vsen .

h ' C h ' cos  C h ' sen C h C  m0V cos   m0V  m0Vsen P  P'  PE .

h ' C h ' cos  C h ' sen C h C  m0V cos   m0V  m0Vsen h h '  cos    m0V cos  C C .

h ' C h ' cos  C h ' sen C h C  m0V cos   m0V  m0Vsen C h h    ' cos    m V cos  0 C C C .

2  ' h .h ' C h ' cos  C h ' sen C h C  m0V cos   m0V  m0Vsen h  cos    m0V cos  …Ec.

h ' C h ' cos  C h ' sen C h C  m0V cos   m0V  m0Vsen h ' sen   m0Vsen C .

h ' C h ' cos  C h ' sen C h C  m0V cos   m0V  m0Vsen h C C  sen   m Vsen 0 .

3 .h ' C h ' cos  C h ' sen C h C  m0V cos   m0V  m0Vsen h  sen   m0Vsen …Ec.

2  ' h sen   m0Vsen  …Ec.…Ec.1 h  cos    m0V cos  …Ec.COMBINANDO ADECUADAMENTE TRES ECUACIONES: LAS h   m0 c(   1 )  ' h h ….3 .

SE OBTIENE: h   (1  cos  ) m0C DONDE: h 12  C  2.43  10 m m0C .